Exosome Circuitry During (De)(Re)Myelination of the Central Nervous System - Domingues, Helena S.; Falcão, Ana Mendanha; Mendes-Pinto, Inês; Salgado, António J.; Teixeira, Fábio G. (Frontiers in Cell and Developmental Biology, 2020)
Reciprocal neuron-glia cell communication is fundamental for proper function of the nervous system. Oligodendrocytes are the glial myelinating cells of the central nervous system (CNS) that insulate and provide trophic support to neurons. This effective interaction is crucial not only for myelination, but also for long-term axonal survival and neural connectivity. In recent years, exosomes have been portraited as key players in intercellular interaction in the context of the healthy and diseased CNS. They act as communicating vehicles, true attachés operating between neurons and glial cells. Despite the complex exosome circuitry within the nervous system, experimental evidence supports the role of exosomes in modulating myelination. Oligodendrocytes secrete exosomes in response to neuronal signals in an electric activity-dependent manner. These released exosomes are then internalized by neurons, contributing to their integrity and activity. In turn, neurons secrete exosomes to control the communication between them and with myelinating cells in order to regulate synaptic function in neuronal development, myelin maintenance and neuroregeneration. In this review, we provide a critical view of the current understanding on how exosomes either from CNS-resident cells or from the periphery contribute to the formation and maintenance of myelin. Also, how the differential content of exosomes in normal and pathological conditions foresees the use of these nanovesicles as putative diagnostic and/or therapeutical agents in white matter degeneration-associated diseases.